Asymmetric Relationship Between Mid-latitude Eurasian Circulation and Summer Rainfall in Hong Kong in Different Phases of ENSO - Li, Yana; Cheung, Ho-Nam; Zhou, Wen (Frontiers in Earth Science, 2021)
During the period 1979–2019, the interannual variation of summer rainfall in Hong Kong (HK), located on the South China coast, is weakly correlated with tropical forcing, including the El Niño/Southern Oscillation (ENSO). Instead, HK summer rainfall is strongly correlated with the mid-latitude circulation over the Urals and the preceding spring sea surface temperature (SST) over the North Atlantic (SST-Atl). The above relationship is stronger in negative ENSO summers, where the SST-Atl anomaly tends to persist from spring to summer. The persistence of the warm SST-Atl anomaly is associated with a Rossby wave train propagating from the North Atlantic to East Asia, with a low over the Urals and a high over the high latitudes of Asia. Correspondingly, the upper-tropospheric westerly jet in East Asia becomes stronger and shifts southward toward South China. The enhanced westerly wind over South China is accompanied by an anomalous Philippine Sea anticyclone, which transports more water vapor to the South China coast and causes more rainfall in HK. On the other hand, during positive ENSO summers, HK summer rainfall is affected by variation in the subtropical westerly jet over South China, which is related to water vapor transport from the Indian Ocean and Bay of Bengal. This is also associated with a height anomaly over northeastern China and the spring sub-polar North Atlantic SST. Therefore, it is important to investigate the impact of mid-latitude forcing on summer rainfall on the South China coast.